Evaluation of the Plant Growth Promotion Effect of Bacillus Species on Different Varieties of Tomato (Solanum lycopersicum L.) Seedlings - Gebeyehu Yibeltie Mengistie; Zewdu Teshome Awlachew (Advances in Agriculture)
Tomato is the most widely eaten vegetable and used as a good source of vitamins A, B, C, and D and minerals such as calcium, phosphorus, and iron. The study was done to evaluate the effect of Bacillus species isolated from the sediment of Lake Tana on the early growth of different tomato (Solanum lycopersicum L.) varieties. All Bacillus isolates significantly (P<0.05) increased the growth of all three tomato varieties in terms of shoot length, shoot fresh weight, shoot dry weight, root length, and fresh and dry weights of the root. The isolates’ efficacy varied among tomato varieties. Bacillus isolate B2 was more effective in the Maya variety, with a potency of 85% and 71.2% shoot and root lengths, respectively. Bacillus isolate B3 was more efficient in the Melkesalsa variety, with a shoot and root length efficiency of 57% and 68%, respectively. Bacillus isolate B1 was more successful in the Kochero variety with 65 and 70% shoot and root length efficacy. Individual isolates’ PGPR characteristics differed, resulting in a wide range of effectiveness among different varieties. More research studies are needed to fully know the mechanism of action and efficacy of these isolates in the field. The isolates must also be identified using molecular techniques.